Cervical cancer: Can it be prevented? - Aggarwal, Pakhee (Baishideng Publishing Group Inc, 2014)
Cervical cancer prevention requires a multipronged approach involving primary, secondary and tertiary prevention. The key element under primary prevention is human papilloma virus (HPV) vaccination. So far, only prophylactic HPV vaccines which prevent HPV infection by one or more subtypes are commercially available. Therapeutic HPV vaccines which aid in clearing established infection are still under trial. Secondary prevention entails early detection of precancerous lesions and its success is determined by the population coverage and the efficacy of the screening technique. A number of techniques are in use, including cytology, visual inspection (using the naked eye, magnivisualizer, acetic acid and Lugol’s iodine), HPV testing and a combination of these methods. Updated screening guidelines have been advocated by the American Cancer Society in light of the role of HPV on cervical carcinogenesis. Recent research has also focussed on novel biomarkers that can predict progression to cancer in screen positive women and help to differentiate those who need treatment from those who can be left for follow-up. Last but not the least, effective treatment of precancerous lesions can help to reduce the incidence of invasive cervical cancer and this constitutes tertiary prevention. A combination of these approaches can help to prevent the burden of cervical cancer and its antecedent morbidity and mortality, but all of these are not feasible in all settings due to resource and allocation constraints. Thus, all countries, especially low and middle income ones, have to determine their own cocktail of approaches that work before we can say with certainty that yes, cervical cancer can be prevented.